Molecular identification of the role of voltage-gated K+ channels, Kv1.5 and Kv2.1, in hypoxic pulmonary vasoconstriction and control of resting membrane potential in rat pulmonary artery myocytes - Archer, S L; Souil, E; Dinh-Xuan, A T; Schremmer, B; Mercier, J C; El Yaagoubi, A; Nguyen-Huu, L; Reeve, H L; Hampl, V (The Journal of clinical investigation, 1998)
Hypoxia initiates pulmonary vasoconstriction (HPV) by inhibiting one or more voltage-gated potassium channels (Kv) in the pulmonary artery smooth muscle cells (PASMCs) of resistance arteries. The resulting membrane depolarization increases opening of voltage-gated calcium channels, raising cytosolic Ca2+ and initiating HPV. There are presently nine families of Kv channels known and pharmacological inhibitors lack the specificity to distinguish those involved in control of resting membrane potential (Em) or HPV. However, the Kv channels involved in Em and HPV have characteristic electrophysiological and pharmacological properties which suggest their molecular identity. They are slowly inactivating, delayed rectifier currents, inhibited by 4-aminopyridine (4-AP) but insensitive to charybdotoxin. Candidate Kv channels with these traits (Kv1.5 and Kv2.1) were studied. Antibodies were used to immunolocalize and functionally characterize the contribution of Kv1. 5 and Kv2.1 to PASMC electrophysiology and vascular tone. Immunoblotting confirmed the presence of Kv1.1, 1.2, 1.3, 1.5, 1.6, and 2.1, but not Kv1.4, in PASMCs. Intracellular administration of anti-Kv2.1 inhibited whole cell K+ current (IK) and depolarized Em. Anti-Kv2.1 also elevated resting tension and diminished 4-AP-induced vasoconstriction in membrane-permeabilized pulmonary artery rings. Anti-Kv1.5 inhibited IK and selectively reduced the rise in [Ca2+]i and constriction caused by hypoxia and 4-AP. However, anti-Kv1.5 neither caused depolarization nor elevated basal pulmonary artery tone. This study demonstrates that antibodies can be used to dissect the whole cell K+ currents in mammalian cells. We conclude that Kv2. 1 is an important determinant of resting Em in PASMCs from resistance arteries. Both Kv2.1 and Kv1.5 contribute to the initiation of HPV.